Corporate Transparency: A Perspective from Thomas Aquinas’ Summa Theologiae - Neves, João César das (Journal of business ethics, 2013)
This article analyzes the issue of organizational transparency through the lens of Thomas Aquinas’ ethics. It provides moral justification for current claims about corporate transparency and sheds light on the ethical values and virtues affecting information disclosure decisions. Transparency is conceptualized as an informational mechanism necessary for performing the virtues of truthfulness, justice, and prudence. This article extends the organizational transparency and corporate social responsibility literatures by providing an alternative moral justification grounded in virtue-based theory, which extends our understanding of the information disclosure decisions made by management.